Analysis of the Problem of Providing Assistance to Poor Families in the Family Hope Program A Case Study of Jagakarsa District - Ahmad Rofiuddin; Fentiny Nugroho (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The Family Hope Program (PKH) is one of the main instruments of social protection policies in Indonesia that aims to reduce poverty through conditional social assistance. However, in its implementation, this program still faces various problems related to the accuracy of the aid distribution targets, especially in urban areas such as Jagakarsa District, South Jakarta. This study aims to analyze various problems in the distribution of PKH social assistance, assess their impact on the effectiveness of poverty alleviation, and identify strategies that can ensure targeted assistance. The approach used is qualitative descriptive with a case study method, through data collection techniques in the form of in-depth interviews, participatory observations, and documentation of PKH companions, Beneficiary Families (KPM), and village officials in Jagakarsa District. The results of the study show that although PKH has provided real benefits for most KPMs, its implementation is still constrained by inaccurate data, limited capacity of companions, low digital literacy, and weak coordination between agencies. On the other hand, targeted distribution of assistance has been proven to increase access to education and health, improve household economic conditions, and encourage behavioral changes towards independence. Therefore, an integrated strategy is needed including strengthening the capacity of social companions, digitizing the distribution system, active community participation, and local culture-based empowerment education to ensure the long-term effectiveness of PKH in reducing poverty rates.